Profitability of momentum strategies in commodity futures markets - Aalto, Antti (My University, 2003)
This study analyzes the profitability of medium-term momentum strategies and provides evidence of the profitability of simple momentum strategies in commodity futures markets using the Goldman Sachs Commodity Index. The purpose of this study is to conduct a comprehensive examination of tactical asset allocation and to illustrate how straightforward management adds value to investors’ commodity futures portfolio over the long only passive investment and what is the role of these strategies when diversification benefits is needed the most. To investigate momentum strategies in commodity futures markets, this thesis focus on daily observations of the Goldman Sachs Commodity Index during the period of January 1998 to December 2006. Furthermore, the strategies are analyzed against the performance of the S&P 500 Composite Index, the U.S. Government Bonds Index and the GSCI. This thesis focuses on simple ways of estimating the momentum effect which minimizes the possibility of the profits be a result of data snooping. To keep the number of combinations examined reasonable this thesis examines the profitability of 10 medium-term momentum strategies with four ranking periods (1, 3, 6, and 12 months) and four holding periods (1, 3, 6, and 12 months) in commodity futures markets. A multifactor model is applied to examine whether the returns generated by the strategies are due to the risk characteristics of the strategies. The main finding of the study is that momentum strategies generate highly significant positive returns for short and intermediate time horizons, and the returns earned by these strategies are close in magnitude to those that have been reported in stocks. The findings of this study also highlight the need for active management of a commodity futures portfolio. Our tactical allocation in commodity futures markets generates an average return of 8.96% a year. The momentum returns are also found to have low correlations with the returns of traditional asset classes, making therefore relative-strength portfolios good candidates for inclusion in well-diversified portfolios.
Keywords: Commodity futures; momentum strategy; diversification; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|